2019
DOI: 10.1186/s13048-019-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of ovarian carcinosarcoma with squamous cell carcinoma

Abstract: Background Ovarian carcinosarcoma, which contains sarcomatous and carcinomatous components, is a very rare tumor. The carcinomatous component is often adenocarcinoma, and squamous cell carcinoma is extremely rare. We herein report a case of ovarian carcinosarcoma in which the carcinomatous component was squamous cell carcinoma. Case presentation A 68-year-old woman presented with a huge ovarian tumor with a clinical diagnosis of malignant tumor of the ovary. She underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…One case reported by Vernadakis et al [ 3 ] showed a giant mass of 33 × 22 × 10 cm in size containing both solid and cystic elements. In our study, the five tumors were unilateral, cystic-solid masses, and the largest transverse diameter ranged from 11 cm to 14 cm, which was similar to reports indicating that the size of masses generally [ 3 , 4 , 6 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…One case reported by Vernadakis et al [ 3 ] showed a giant mass of 33 × 22 × 10 cm in size containing both solid and cystic elements. In our study, the five tumors were unilateral, cystic-solid masses, and the largest transverse diameter ranged from 11 cm to 14 cm, which was similar to reports indicating that the size of masses generally [ 3 , 4 , 6 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Many ovarian tumors manifest as large pelvic masses. Clinical, some studies showed that patients with OCS are more likely to present with a unilateral, large pelvic mass [ 4 , 6 , 13 ]. The radiological findings of OCS are not well known, as few studies have described the imaging feature of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovarian carcinosarcoma (OCS), also known as malignant mixed Müllerian tumour (MMMT), is one of the rarest histological subtypes of ovarian cancer. OCS represents 1–4% of all ovarian tumours [ 2 , 3 ]. OCS can be found in the genito-urinary tract with the most common site being the uterus, followed by the ovary, fallopian tubes, cervix, vagina, peritoneum, breast and urethra [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%